2008
DOI: 10.1038/sj.jp.7211926
|View full text |Cite
|
Sign up to set email alerts
|

The early use of minimal enteral nutrition in extremely low birth weight newborns

Abstract: Objective: To gather information regarding the efficacy of early minimal enteral nutrition on overall feeding tolerance in extremely low birth weight infants.Study Design: Prospective randomized controlled trial comparing the early use of minimal enteral nutrition in extremely low birth weight infants from day 2 to day 7 vs control infants. On day 8, feeding volume in both groups were advanced by 10 ml kg À1 day À1 until full enteral feedings were reached. Time to full feeds, number of intolerance episodes, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0
1

Year Published

2009
2009
2014
2014

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 20 publications
0
13
0
1
Order By: Relevance
“…Schanler et al found that the incidence of NEC between the groups was similar and that gut priming did not have the beneficial effect of reducing the risk for NEC. 29 A study by Mosqueda et al 30 comparing feeding intolerance in extremely low birth weight infants who received gut priming between DOL 2 to 7 versus remaining NPO observed the incidence of NEC to be similar between the 2 groups.…”
Section: Discussionmentioning
confidence: 99%
“…Schanler et al found that the incidence of NEC between the groups was similar and that gut priming did not have the beneficial effect of reducing the risk for NEC. 29 A study by Mosqueda et al 30 comparing feeding intolerance in extremely low birth weight infants who received gut priming between DOL 2 to 7 versus remaining NPO observed the incidence of NEC to be similar between the 2 groups.…”
Section: Discussionmentioning
confidence: 99%
“…Units included in two recent RCTs assessing prolonged minimal enteral feeding13 15 commenced enteral feeding much later (median 9 days of life)13 than units responding to our survey, or achieved full feeds very late (median 32 days of life) 15. Large cohort studies of extremely low birthweight (ELBW) infants exclusively fed human milk indicate that early introduction and rapid advancement of feeds are not associated with high rates of NEC,2022 and that it is possible to establish full enteral feeds by the third week of life in the majority of ELBW infants 23.…”
Section: Discussionmentioning
confidence: 99%
“…Many systematic reviews include small numbers of infants in patient populations different to those considered high risk today 1012. Some recent randomised controlled trials (RCTs) also have limited generalisability in units where practice falls outside the RCT study protocols 1315…”
Section: Introductionmentioning
confidence: 99%
“…In summary, the authors suggest starting trophic feeds early, not advancing at first, then advancing reasonably rapidly. Interestingly no advantage was found for trophic feeding in a randomised controlled trial of extremely low birthweight infants 8. This latter trial is useful as it was carried out with babies entering the era of antenatal steroids and postnatal surfactant and therefore reflects a more contemporary population; compared to older studies carried out in the 1980s and early 1990s 7.…”
Section: How To Progressmentioning
confidence: 99%